HUBUNGAN SELF-ESTEEM DENGAN PERILAKU ALTRUISME ANAK USIA 5-6 TAHUN DI TK PEMBINA KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Cintami, Putri; Novianti, Ria; Kurnia, Rita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to find out the relationship between Self-Esteem and Altruisme Behavior of children aged 5-6 years at the Pembina Sub-district of Bukit Batu, Bengkalis Regency. As for the population in this study were all the Kindergarten Students of Bukit Batu Subdistrict, Bengkalis Regency, which numbered 58 children taken using saturated sampling techniques. the method used is Pearson Product Moment correlation to see the relationship between the variables Self-Esteem and children's Altruisme Behavior. In this study the data collection technique used is the observation method by giving a check list to the column where the event appears. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows ver.21. Based on hypothesis there is any significant positive correlation between self-esteem and altruisme behavior of children aged 5-6 years in the Pembina Sub-District of Bukit Batu, Bengkalis Regency. It could be see from the result of corellation coefficient that rxy = 0,504 and significant level is 0,00<0,05. The level of correlation between Self-Esteem and altruisme behavior of children is in the middle category with the rank of determinant coefficient in the amount 25,4%, it means the Self-Esteem intilligence principalaffect Altruisme Behavior of children much 25,4%.Key Words: Self-esteem, altruisme behavior